A CD47 antibody with minimized erythrocyte and thrombocyte toxicities - Pei, Min; Dai, Xiao-Dong; Jiang, Xiao-Fan; Yuan, Cai-Yi; Tan, Jie; He, Kai-Feng; Liu, Guo-Jian; Zhu, Jin-Di; Li, Huan-Huan; Pan, Ai-Ling; Wang, Ya-Ru; Chen, Yi-Li; et al. (Frontiers in Oncology, 2025)
IntroductionBlockade of the CD47/SIRPa axis has emerged as a promising approach to enhance macrophage-mediated anti-tumor activities in cancer immunotherapy. However, the clinical application of early CD47 antibodies has been associated with significant hematotoxicities, including hemagglutination, anemia, and thrombopenia. Although several CD47 antibodies have generally avoided hemagglutination, anemia, and thrombopenia remain, potentially mediated by enhanced phagocytosis of erythrocytes and thrombocytes.Methods1B2–10 is a humanized CD47-neutralizing antibody generated by mouse immunization and phage display technology. Its efficacy and safety were evaluated using in vitro assays, tumor xenograft models, and studies in cynomolgus monkeys. In silico modeling and mutagenesis analyses were performed to identify the 1B2-10 binding epitopes.ResultsIn vitro, 1B2–10 exhibited minimized binding to erythrocytes and thrombocytes, did not induce hemagglutination, and reduced erythrocyte phagocytosis. It enhanced macrophage-mediated phagocytosis of tumor cells and showed potent antitumor effects as a monotherapy or in combination with a PD-1 antibody in tumor models. In cynomolgus monkeys, single doses of 1B2–10 at 120 mg/kg and repeated doses at 100 mg/kg were well-tolerated, with no significant hematological toxicities observed. In silico studies revealed the molecular basis for reduced erythrocyte binding, demonstrating that two critical N-linked glycans sterically masked epitopes.DiscussionThese findings suggest that 1B2-10 demonstrates a favorable efficacy and safety profile, indicating great therapeutic potential for cancer. Based on these studies, 1B2–10 has been renamed as DS003 and is currently advancing through Phase I clinical trials in China to further evaluate its safety profile and preliminary efficacy in human subjects.